The importance of reading in the education of people deprived of their liberty - Eveliny Almeida Feitosa Jácome; Selma Maria Abdalla Dias Barbosa (Universidade Federal do Norte do Tocantins, 2024)
Discussing education for individuals deprived of their freedom is a controversial topic. However, it provides the opportunity for the emergence of other paths and possibilities for further research in the area. The interest in the topic arose after learning about the Clube dos Livres extension project, from the Federal University of Northern Tocantins, developed at the Tocantinópolis Penal Unit with people deprived of liberty. This article, co-authored with the Advisor, is an excerpt from the research developed from a case study of the extension project. Thus, it is proposed to identify the meanings attributed by project participants to experiences with reading in prison, discuss some understandings of the rights attributed to these subjects, inside and outside prison, and how reading has the power to enhance the formation of readers even within an exclusionary space that is unfavorable for learning. We are looking for theorists who discuss literature and human rights aimed at people in situations of extreme vulnerability, as is the case of prisoners, aiming to answer the following question "How does reading, as an instrument of remission of sentence, contribute to the reading formation of subjects who have been in a situation of deprivation of liberty in the Tocantinópolis Penal Unit? To this end, qualitative research was developed, with an interpretative nature, within the area of ​​Applied Linguistics (LA), using for this purpose semi-structured interviews that captured the perception of the subjects investigated with their experiences and how the educational processes experienced in prison contributed to live in society so that they felt included or not in society.